One size doesn’t fit all: regional dynamics in pediatric emergency visits during the SARS-CoV-2 pandemic - Seiler, Michelle; Biland, Gregory; Gruebner, Oliver; Manzano, Sergio; Gualco, Gianluca; Sidler, Marc; Laasner, Ursula; Dratva, Julia; von Rhein, Michael (Frontiers in Public Health, 2025)
Background and aimsThe Swiss government implemented lockdown measures during the COVID-19 pandemic to contain outbreaks and prevent healthcare system overload. Emergency department (ED) visits were discouraged, leading to a decline in utilization, except for urgent cases. However, little is known about regional variations in pediatric ED use and spatial distribution patterns across Switzerland. This study aimed to analyze changes in pediatric ED catchment areas over time across three Swiss centers and explore implications for future healthcare crises.MethodsWe conducted a retrospective, longitudinal cohort study at three tertiary pediatric EDs in Zurich, Bellinzona, and Geneva, covering different language regions. Data from March 2018 to February 2022 included daily pediatric ED visits, patient demographics, and postal codes. We categorized the timeline into pre-pandemic (before March 11, 2020), pandemic (March 11, 2020 – March 22, 2021), and post-pandemic (after March 22, 2021) phases. Travel distances were analyzed using driving distance matrices along the Swiss road network, and geovisualization techniques were applied to illustrate regional variations and policy impacts.ResultsAmong 294,409 recorded ED visits (158,643 in Zurich, 32,332 in Bellinzona, 103,434 in Geneva), ED visits declined by approximately 50% during the lockdown. Before the pandemic, patients living closer to hospitals visited more frequently. During the pandemic, the decline was most pronounced among nearby residents, while post-pandemic utilization shifted toward patients living farther away. Regional differences were observed: travel distances remained stable in Zurich; in Bellinzona, they increased by nearly 11%; and decreased by 3% in Geneva.ConclusionThe pandemic significantly influenced pediatric ED utilization in Switzerland, with long-term shifts in healthcare-seeking behavior. Despite uniform national regulations, utilization patterns varied across language regions, suggesting multifactorial influences. Geographic visualization provided insights into catchment area changes, offering a valuable tool for healthcare planning. These findings highlight the need for region-specific strategies in future healthcare crises, and our approach can be applied to other Swiss regions and similar global settings.